Valency of the noun pyktis ʻangerʼ in the Corpus of Contemporary Lithuanian Language - Čižik-Prokaševa, Veslava (Kalbotyra, 2025)
By using methods of interpretation, descriptive analysis, grammatical analysis, semantic and lexical analysis, 292 sentences containing different forms of the noun pyktis ʻangerʼ drawn from the Corpus of Contemporary Lithuanian Language were analysed. The research showed that the syntactic valency of the noun pyktis ʻangerʼ partly differs from that of the verb pykti(s) ‘to be angry (with)ʼ. The findings indicate that the syntactic valency of the noun pyktis ʻangerʼ is influenced by the semantics and grammar of the verb pykti(s) ‘to be angryʼ and nouns within its minimal semantic field. Specifically, the nominative case governed by the verb pykti(s) ‘to be angryʼ is replaced by the genitive case governed by the noun pyktis ʻangerʼ. Similar to the verb pykti(s) ‘to be angryʼ, the noun pyktis ʻangerʼ requires constructions such as ant ʻonʼ + genitive, dėl ʻbecause ofʼ + genitive, už ʻforʼ + accusative, su ʻwithʼ + instrumental and a subordinate clause. Furthermore, pyktis ʻangerʼ, like priešiškas ʻhostileʼ, jausmas ʻfeelingʼ, nusistatymas ʻattitudeʼ and piktumas ʻmaliceʼ, requires a dative actant and can take a construction with atžvilgiu ʻin relation toʼ instead of the dative. Similar to nusistatymas ʻattitudeʼ, pyktis ʻangerʼ can take a construction with prieš ʻagainstʼ and tarp ʻamongʼ.The noun pyktis ʻangerʼ has the same semantic valency as the verb pykti(s) ʻto be angryʼ, just there are more ways to express the contentive and the percipient. When a person, who is experiencing anger, is mentioned or emphasized in a sentence, the noun pyktis ʻangerʼ agrees with the genitive or is used in a construction with tarp ʻamongʼ percipient. When the noun pyktis ʻangerʼ agrees with a dative or is involved in constructions with ant ʻonʼ, prieš ʻagainstʼ or atžvilgiu ʻin relation toʼ contentive, it expresses a content of state. When the cause is actualized in a sentence, pyktis ʻangerʼ agrees with the construction dėl ʻbecause ofʼ + genitive causative, whereas, when the reason is highlighted, it is used with the construction už ʻforʼ + accusative motive. However, it can describe a peripheral person, in this case pyktis ʻangerʼ agrees with the construction su ʻwithʼ + instrumental comitative.The collected examples show that the semantic valency of pyktis ʻangerʼ is more diverse than that of the verb. A genitive actant can indicate not only humans, but objects or abstract concepts too. An anger can be directed towards anything: humans, animate and inanimate objects, or abstract concepts. Nonetheless, a construction su ʻwithʼ + instrumental is not unique to humans, it can indicate abstract concepts too.Hence the noun pyktis ʻangerʼ inherits the valency of verbs pykti(s) ʻto be angryʼ, while also acquiring new properties from nouns within its minimal semantic field.